Aplikasi Pembelajaran Matematika “MatAsik” Untuk SD/MI Berbasis Android Menggunakan Kodular - Ningsih, Nuning Melia; Harjono, Harjono; Purbasari, Dita Anggi; Ulya Dhina, Karina Octamardia (Jurnal Ilmiah SINUS, 2025)
The development of technology, especially computers, can be used as a tool to create learning media, while mobile phones, especially Android-based ones, can be used as a means to deliver learning media. Based on interviews and observations in class, the researcher concluded that teachers have not been optimal in using learning media so that students are interested in learning, especially mathematics. Therefore, the creation of Android-based Mathematics learning media can make learning easier, more fun and more practical. This learning application is designed to be simple, efficient and easy to operate by users, especially elementary school students. This study aims to create an Android-based mathematics learning application using the class V code for elementary schools/Islamic elementary schools as an independent learning medium and to help increase students' interest in learning. The research method used is the extreme programming method which includes the stages of planning, design, coding, and testing which are calculated based on the Likert scale.  The results of the study showed that the average respondent strongly agreed that the application is suitable for use as an alternative android-based mathematics learning media using Kodular with the hope that students are happy and motivated to learn mathematics.